LAPAROSCOPIC PYELOPLASTY IN YOUNG CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article presents considerations and considerations for laparoscopic pyeloplasty in young children. Laparoscopic pyeloplasty is a low-traumatic surgical operation used to solve problems related to the restoration of the pyelourethral segment. It is an effective and efficient alternative compared to open surgery and endopyelotomy. Objectives: To improve methods of surgical treatment of congenital hydronephrosis in young children. Research: 2016-2022. 70 children (1-5 years old) with hydronephrosis underwent laparoscopic pyeloplasty. The results were compared with a group of children who underwent open surgery between 2002 and 2016. Results. Laparoscopic pyeloplasty is a safe operation for sick children with good anatomical features. Advantages of laparoscopic pyeloplasty: minimal trauma: performed with several small incisions. Fast recovery: post-operative pain is minimal and the recovery process is quick. Aesthetic result: small incisions leave small scars. It is recommended that the operation be performed by well-trained professionals. Conclusion: The results of endosurgical interventions confirm the highest efficiency of laparoscopic pyeloplasty in children, as well as its low morbidity when using an antegrade internal drainage stent or pyeloplasty catheter.